Implementasi Program Cek Kesehatan Gratis Di Pelayanan Kesehatan Primer: Studi Literatur - Syafrina Ulfah; Nurcholisah Fitra (STIKES Columbia Asia Medan, 2026)
The Free Health Check-up (CKG) is a government program designed to strengthen promotive and preventive health efforts through the early detection of risk factors, pre-disease conditions, and diseases across the community according to the life-cycle approach. As a relatively new initiative, the implementation of the CKG program in primary healthcare settings still requires further evaluation to assess implementation readiness, digital support systems, and community participation. This literature review aimed to examine the implementation of the Free Health Check-up Program in primary healthcare services. Relevant literature was retrieved from the Google Scholar database using the keyword